Anatomical Description of the Duct System of the Pancreas: A Cadaveric and Magnetic Resonance Cholangiopancreatography Study - Anjali Singh; Suraj Prakash; Shaifaly Madan Rustagi (Journal of Medical Academics)
Introduction: Variations in the duct system of the pancreas lead to anomalies that predispose to diseases like acute or chronic pancreatitis or impairment of the pancreatic exocrine function. Pancreas divisum is the most common ductal anomaly leading to chronic pancreatitis. Objectives: This study was aimed at observing, understanding, and analyzing recorded variations of the ductal anatomy of the pancreas with the purpose of reviewing the literature on pancreatic duct anatomy, and underlining its importance in daily invasive endoscopic and surgical practice. Methods: A total of 10 cadaveric pancreas and duodenum were obtained en bloc from the abdomen. Following the injection of eosin dye for better visualization of the ducts, piecemeal dissection of the parenchyma of the gland was carried out to expose the duct system of the pancreas. A total of 10 outpatient department (OPD) cases of pancreatitis from the department of radiology in whom MRCP had been performed were chosen at random. The findings were interpreted, tabulated, compared with outcomes of previous studies, and analyzed. Result: Our findings from the cross-sectional observational study suggest that out of twenty pancreas, 75% of cases showed the presence of major pancreatic ducts, and 25% of cases showed the presence of both main and accessory pancreatic ducts. MRCPs of patients with acute/chronic pancreatitis obtained from the Department of Radiology showed the presence of a single duct, suggesting that presence of single duct anatomy might be a predisposing condition for the occurrence of pancreatitis. Conclusion: This knowledge is significant for planning diagnostic procedures and procedure-related complications. Magnetic resonance cholangiopancreatography (MRCP) is the investigation of choice for visualizing the pancreatic and biliary ductal anatomy as it is noninvasive and safe. Hence, based upon findings of the pancreatic ductal system using cadaveric pancreas and MRCP, associations between the patterns and anomalies with pancreaticobiliary diseases were assessed.